The role of creative learning resource design in enhancing literacy and numeracy skills: A study of the Kampus Mengajar program - Nisa, Dini Khoirun; Jaya, Christian Arief (Indonesian Journal of Curriculum and Educational Technology Studies, 2024)
This study aims to explore the relationship between creativity in learning resource design and the improvement of literacy and numeracy skills among students in the Kampus Mengajar Program, Batch 7. Specifically, the study seeks to: 1) identify the correlation between creativity in learning resource design and literacy, and 2) examine the relationship between creativity in learning resource design and numeracy. Employing a quantitative research design, the study uses a product-moment correlation method with a non-probability sampling approach, consisting of 30 students. Data were collected through a Google Forms questionnaire, and prerequisite tests, including normality and linearity tests, were conducted. Hypothesis testing was performed using a correlation test. The results reveal a statistically significant positive relationship between creativity in learning resource design and literacy (Sig. = 0.027 < 0.05), as well as between creativity in learning resource design and numeracy (Sig. = 0.019 < 0.05). These findings suggest that creative learning resource design developed by students in the Kampus Mengajar program plays a key role in enhancing both literacy and numeracy skills in schools. The study contributes to the understanding of effective teaching strategies within the Kampus Mengajar Program and highlights the importance of creative approaches in addressing educational challenges.